Slavery and religious conversion in Portugal's Indian empire, 1500-1700 - Hassell, Stephanie (Indian Ocean studies, 2025)
"In the sixteenth and seventeenth centuries, enslaved Africans and Asians were crucial to expanding the Portuguese Catholic empire. The Crown and Church mandated their conversion, expanding the Christian population and securing anti-Muslim allies. Inquisition records from Goa highlight the complex dynamics of conversion, slavery, and imperial ambitions"-- Provided by publisher